Handedness and Birth Order Among Heterosexual Men, Gay Men, and Sao Praphet Song in Northern Thailand - Malvina N. Skorska (2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature. Previous research has examined handedness and birth order to inform sexual orientation and gender identity/role expression development; however, sexual orientation and gender identity/role expression have rarely been disentangled to provide a more nuanced perspective. In Thailand, we investigated sexual orientation and gender identity simultaneously via comparison of 282 heterosexual men, 201 gay men, and 178 sao praphet song—i.e., androphilic, markedly feminine males recognized as a “third” gender. Handedness was examined as: extremely left-handed, moderately left-handed, ambidextrous, moderately right-handed, or extremely right-handed. Birth order was examined as numbers of older and younger brothers and sisters, by using Berglin’s, fraternal, and sororal indices, and by examining the older brother odds ratio and sibling sex ratio. Compared with heterosexual men, gay men and sao praphet song were more likely to be extremely right-handed. Sao praphet song were also more likely to be extremely left-handed than heterosexual and gay men. Heterosexual men and sao praphet song had later sororal birth order compared with the expected Thai population value, suggesting stopping rules influenced when probands’ mothers ceased having children. These findings provide new insights and replicate previous findings in a non-Western sample. Regarding handedness, in males, mechanisms related to extreme right-handedness likely influence the development of androphilia, whereas mechanisms related to both extreme right- and extreme left-handedness likely explain the combination of androphilia and feminine gender identity/role expression. Regarding birth order, similar to the conclusions of some prior research, stopping rules pose a challenge for testing the fraternal birth order effect.